Zooplankton community structure, population dynamics and production and its relation to abiotic and biotic factors in Lake Ziway, Ethiopia - Dagne, Admassie Adamneh (2010)
Quantitative Langzeituntersuchungen über das Zooplankton äthiopischer Gewässer, deren Probenentnahmen in kurzen Zeitintervallen erfolgten, sind eher selten, Angaben über die Sekundärproduktion sind eine Rarität. Aus diesem Grunde wurde das Zooplankton im See Ziway, einem trüben Flachsee des ethiopischen Grabenbruches, untersucht, die saisonale Entwicklung und die steuernden abiotischen und biotischen Faktoren beschrieben und die planktische Sekundärproduktion der wichtigsten Vertreter der Zooplanktongemeinschaft berechnet. Die Untersuchungen wurden von Oktober 2008 bis September 2009, basierend auf 14-tägigem Probenintervall, durchgeführt; die Probenentnahmen erfolgten mit einem 10-Liter Schindler-Schöpfer und Planktonnetzen einer Maschenweite von 40 und 100 µm. Trockengewichte und Entwicklungszeiten der einzelnen Arten und Entwicklungsstadien wurden im Labor ermittelt. Die Verbindung der Feld- mit den Labordaten ermöglichte die Beschreibung der Populationsdynamik und die Berechnung der Sekundärproduktion. Abiotische Parameter wie die Wassertemperatur, Sauerstoff (ausgenommen die Bereiche mit dichtem Makrophytenbewuchs) und pH ließen keine ausgeprägten Unterschiede im Verlaufe der Untersuchung erkennen; dafür zeichnet die fast ständige windbedingte Durchmischung des Wasserkörpers verantwortlich. Die Sichttiefe hingegen ließ klare Unterschiede zwischen Trocken- und Regenzeit erkennen. Der mit den Niederschlägen einhergehende Anstieg der im Wasser suspendierten Partikel ist für den See charakteristisch und führt zu Auswirkungen im physikalisch-chemischen Bereich und in den Lebensgemeinschaften. Das Phytoplankton des Ziway bestand vor allem aus koloniebildenden (Microcystis spp.) und fädigen Arten (Anabaena sp., Oscillatoria sp.). Die Chlorophyll a-Werte schwankten zwischen 6,8 µg.l-1 und 59,4 µg.l-1, die Maxima wurden kurz vor der Regenzeit gemessen. Das Zooplankton des Ziway entsprach den Erwartungen von tropischen Seen, Rotatorien dominierten (49 Arten), 10 Crustaceenarten (3 Cyclops spp., 7 Cladocera) ergänzten die Artenzahl. Die Rotatorien bildeten 43% der Individuendichte, Brachionus spp. und Keratella spp. waren vorherrschend. Thermocyclops decipiens war die wichtigste Crustaceenart, dazu traten die Cladoceren Moina micrura, Diaphanosoma excisum, Ceriodaphnia cornuta und Daphnia barbata in Erscheinung. Große Daphnien und calanoide Copepoden fehlten. C. cornuta und D. barbata verschwanden aus dem Plankton mit abnehmender Sichttiefe. Neu für den Ziway waren die Funde von Pseudosida szalayi und Chaoborus sp. Die Bedeutung der Sammelstrategie und vor allem der zeitlichen Abfolge der Proben-entnahmen konnte durch einen Vergleich von einmonatiger mit 14-tägiger Beprobung aufgezeigt werden. Auch die horizontalen Unterschiede (Uferbereich – offener See) im Vorkommen der einzelnen Arten konnten klar dargestellt werden. So wurde Alona nicht wie in früheren Untersuchungen im Freiwasser vorherrschend gefunden sondern im Uferbereich. Die großen und eitragenden Weibchen von Mesocyclops aequatorialis waren in den Uferbereichen seltener als im Freiwasser. Klare Vertikalverteilungen waren gleichfalls feststellbar. Eitragende Copepoden waren im Freiwasser tagsüber in den tieferen Wasserschichten zu finden, in der Nacht wanderten diese Tiere in die oberflächlichen Wasserschichten. Räuberdruck von Chaoborus und Fischen (Tilapia, catfish) scheint der Auslöser für dieses Verhalten zu sein. Rotatorien und Copepoden bildeten 96% der Zooplanktonabundanz. Die Zooplankton-biomasse (Jahresdurchschnitt: 91 mg dw.m-3) prägten die Copepoden, der Beitrag der Rotatorien und Cladoceren lag bei 14%. Die Cladocerenbiomasse nahm gegen die Regenzeit hin deutlich ab, jene der Copepoden stieg hingegen in der Zeit an. Eine Korrelationsanalyse bestätigt die stark positive Beziehung zwischen zunehmender Sichttiefe (in der Trockenzeit) und Cladocerenbestand und zwischen Chlorophyll a (Maxima knapp vor der Regenzeit) und Copepodenbestand. Für die Dominanz kleiner Arten und junger Entwicklungsstadien scheint der Räuberdruck verantwortlich zu sein. Embryonale und postembryonale Entwicklungszeiten von Ceriodaphnia cornuta, Moina micrura, Mesocyclops aequatorialis und Thermocyclops decipiens wurden experimentell für einen Temperaturbereich von 21,3°C – 25,1°C ermittelt. Kulturen von Diaphanosoma excisum und Daphnia barbata waren nicht erfolgreich. Die Beziehung zwischen Temperatur und den jeweiligen Entwicklungszeiten konnten mit einer quadratischen Regression sehr gut beschrieben werden. Die Ergebnisse stimmten großteils sehr gut mit den Ergebnissen von Populationen aus anderen tropischen Gewässern überein. Die Produktion von Moina micrura, Mesocyclops aequatorialis und Thermocyclops decipiens wurde mittels der „growth increment“ (Winberg)-Methode berechnet. Die beiden Copepoden des Ziway bildeten 84% der Crustaceenproduktion. Die Produktion von M. micrura war während der Trockenzeit 2,3 mal höher als während der Regenzeit, die 2 Copepoden hingegen waren in der Regenzeit doppelt so produktiv wie in der Trockenzeit. Die Jahresproduktion der drei Crustaceen betrug 3,2 g dw.m-3, die Jahres-P/B-Rate 38,7. Die relativ geringe Produktion und die doch hohe P/B-Rate erklären sich aus der Dominanz von kleinen Zooplanktern und deren postembryonalen Entwicklungsstadien (geringe Biomasse) und den, der kontinuierlich hohen Temperatur entsprechenden, kurzen Entwicklungszeiten. „Bottom up“ (Qualität der Nahrung) und „top down“ (Räuberdruck durch Chaoborus und Fische) Kontrolle, hoher Gehalt an suspendierten Partikeln und ein dichter Makrophyten-bestand im Uferbereich sind jene Faktoren, die die Entwicklung des Zooplanktons im Ziway (Populationsstruktur, Vorkommen, Produktion) steuern. Long term quantitative studies on zooplankton of Ethiopian water bodies on the basis of short sampling intervals are still scarce. Information on secondary production is even much more limited. For this reason zooplankton community structure, population dynamics and production was studied in relation to abiotic and biotic factors in Lake Ziway, a shallow turbid Rift Valley lake. Between October 2008 and September 2009 field sampling was performed on a biweekly basis with Schindler sampler (10l) and plankton nets of 40 and 100 µm mesh sizes; data on dry weights and development times of crustaceans were determined in the laboratory and were applied to the field data to describe population dynamics and to estimate secondary production. Abiotic parameters (e.g. water temperature, dissolved oxygen, and pH) did not show marked temporal variation except the dissolved oxygen in the inshore station with dense macrophyte stands. Frequent and well mixing of the water column resulted in very low difference in those abiotic parameters between the upper and lower water stratum. Water transparency (secchi depth) showed significant variation between dry and rainy season. The increase in turbidity following rainfall is clearly a basic limnological feature of the lake that led to a decline in the physical, chemical and biological parameters. The phytoplankton community of Lake Ziway was dominated by large colonial forms like Microcystis species and filamentous, Anabaena and Oscillatoria species. Maximum Chlorophyll a concentration was recorded during the short wet period before the main rains. Species composition of zooplankton in Lake Ziway reflects typical tropical aspects, with rotifers being the dominant taxa (49 species) and 10 crustaceans (3 cyclopoids and 7 cladocerans) contribute the rest. Brachionus and Keratella species were the dominant and major contributors to the total rotifer abundance. Rotifers comprised 43% of the total zooplankton abundance. Crustaceans were dominated by one species Thermocyclops decipiens. Moina micrura, Diaphanosoma excisum, Ceriodaphnia cornuta and Daphnia barbata represent the cladocerans. Larger Daphnia and calanoid species are absent. Change in species composition of zooplankton was evident. Ceriodaphnia cornuta and Daphnia barbata were absent from the plankton following the decline in the water transparency. Pseudosida szalayi and Chaoborus sp. which were not reported from the lake earlier could be identified. Rotifer and copepod species reported in earlier investigations were confirmed by this study. The importance of sampling strategy which considers the development times of the various plankton organisms becomes apparent. Comparison between the temporal distribution patterns of total zooplankton in Lake Ziway from two different sampling intervals (biweekly and monthly) indicates that in the monthly sampling short-term fluctuations in the population were masked, but becomes obvious from the biweekly taken samples. Variations in the horizontal distribution pattern of zooplankton species became obvious, two to five fold abundances of zooplankton could be revealed inshore compared to the offshore station of Lake Ziway. Among the species, the littoral species Alona reported to be dominant in the open water of lakes Ziway and Awassa was not confirmed in the present study. Alona occurred in higher (as high as fivefold) density inshore. On the contrary size variation in the distribution of copepod species was evident, larger adults and egg carrying Mesocyclops aequatorialis females were almost absent from day samples and rare in the inshore station. A clear vertical distribution gradient mainly by the larger and egg carrying copepods was also observed. Numbers of egg carrying females and their clutch size were larger from night samples and increased with depth in the day samples. Predation by fish (catfish) and the invertebrate predator Chaoborus seemed to be the major cause for variation in the distribution. High predation pressure on large sized adults and egg carrying Mescyclops females were evident in the present study; the stomach contents of catfish consisted mainly of the larger copepods and the biomass of adult Mesocyclops, the largest sized among the crustaceans in Lake Ziway, was lower than the biomass of the nauplii. Rotifers and copepods comprised about 96% of the total zooplankton abundance. Zooplankton biomass was dominated by copepods, rotifers and cladocerans comprising only 14% of the annual mean zooplankton biomass (91 mg dwt m-3). Temporal variation of cladocerans biomass was associated with the water transparency with a general decline towards the rainy season, copepods however showed an increase at the same time. Correlation analysis also revealed that standing stocks of cladocerans were highly correlated with water transparency and weakly and negatively with Chlorophyll a concentration. Copepods however correlated best with Chlorophyll a. Predation pressure on the larger zooplankton organisms (e.g. Daphnia barbata and Mesocyclops) shifted zooplankton community structure in Lake Ziway towards the dominance of the smaller sized Thermocyclops, pre-adult copepods and rotifers. Embryonic and post-embryonic development times of Ceriodaphnia cornuta, Monia micrura and two cyclopoid copepods Mesocyclops aequatorialis and Thermocyclops decipiens were determined in the laboratory at mean temperature range of 21,3-25,1 0C. Cultures of Diaphanosoma excisum and Daphnia barbata were not completed successfully. The relationship between temperature and development time of crustaceans was best fitted by quadratic equations. The results on embryonic and post-embryonic development times were comparable with the results from other tropical lakes. Productions of the dominant Cladocera (Moina micrura) and cyclopoid copepods (Mesocyclops aequatorialis and Thermocyclops decipiens) were estimated by growth increment (Winberg) method. Copepods contributed 84% of the total crustacean production in Lake Ziway. Lake Ziway showed well expressed seasonal variation in crustacean production. The production of M. micrura was usually greater during the dry season (2,3 times) than during the wet season. Cyclopoid copepods however showed about 2 fold greater production during the wet season. The total annual crustacean production in Lake Ziway was 3,2 g dw m-3. The mean annual P/B ratio for the dominant crustaceans was 38,7. The dominance of small sized zooplankton as well as high contribution of post-embryonic stages to the total copepod production and relatively uniform high temperature throughout the year and correspondingly short development times result in low production but high turnover rate. Bottom up (quality of food) and top-down (predation by fish and Chaobours) control, turbidity and dense macrophyte in the littoral could be the major factors to govern the zooplankton community structure and productivity of Lake Ziway.